Modification of Searle's Speech Act of Promising in its Application to Selected Religious and Political Texts - أ. د. كاظم حیدر الجوادي رفیدة كمال عبد المجید (College of Education for Women, 2019)
This study presents certain modifications done to the conditions set by Searle (1969: 57) concerning the speech act of promising in order to render them to selected sayings of Prophet Muhammad (P.B.U.H.) and Jesus Christ (P.B.U.H.) and to political texts. These modifications make the conditions of the speech act of promising appropriate for sincere promises made by the Messengers of God since they deliver their Messages of God but they are unable, as Messengers, to fulfill God's promises which they make as part of their Messages and by representatives of States who deliver speeches on behalf of their Governments. These are the only two situations where the speakers can make promises and do not fulfill these promises by themselves according to Searle's conditions of speech act of promising. This is an attempt to fill a gap in Searle's speech act theory.